Safeguarding migrant and refugee children: a critical contemporary challenge - Gerson, Diana; Al Marzooqi, Dana Humaid; Argyriades, Demetrios (Frontiers in Political Science, 2024)
This paper investigates the pivotal role of psycho-social support in bolstering the mental and spiritual well-being of migrant and refugee children. It highlights the necessity to shield these vulnerable groups from spiritual abuse within humanitarian efforts. Remarkably, an estimated 117 million people are currently displaced by conflict, violence, war, and natural disasters, and as of 2023, nearly half of them are under the age of 18. The call, therefore, for culturally sensitive, effective interventions is manifestly urgent. Our research underscores, in order to highlight, the significance of professionalizing faith-based and local faith actors to advocate for standards that mitigate the risks of religious exploitation and safeguard the children’s spiritual identity, practices, and beliefs. We highlight the existing gaps in the literature and propose a framework for further research. Our focus is on the effectiveness of the Global Compact on Refugees and the impact of local versus global policies on the protection and well-being of migrant and refugee children. Our analysis extends to humanitarian agencies’ and caregivers’ best practices and prevention strategies. It further emphasizes the importance of safeguarding neutrality at all times and promoting community reintegration. Our findings call for a concerted effort to enhance professionalism among those working with refugees in humanitarian frameworks, prioritizing children’s spiritual, mental, and physical well-being. This study seeks to contribute to the ongoing discourse on the rights of children on the move. It advocates for policies and practices that recognize their vulnerability and potential for resilience.